Gender Perspective: Procedural Scope of the Colombian Judicial and Health System - Clavijo Cáceres, Darwin; Ibarguen González, Ella Mercedina; Botello Estupiñán, Nidia Julieth; Colorado Bautista, Hernán Darío; Angarita Duarte, Ronald Emerson; Nobman Montes, Yustin Yesid; Araque Chacón, Andrea Carolina; Hernández Hernández, Lina Paola; Hernández Caicedo, Diego Alberto; Lastra Benavides, Claudia Irene; Duarte Contreras, William Javier; Segura Ibarra, Ana María (Sello Editorial Unipamplona, 2025)
The incorporation of a gender perspective into the Colombian judicial and healthcare systems constitutes one of the most significant advances in the pursuit of a more equitable and inclusive society. This approach recognizes that gender-based power relations generate inequalities that affect people’s lives, especially those who have historically been discriminated against, such as women, non-binary individuals, and other vulnerable groups. However, although significant regulatory progress has been made, there is still a long way to go, especially in the cultural transformation necessary for this perspective to be effective in the legal context and in the healthcare system. Throughout this book, the study of women as central subjects is prioritized, both in the judicial procedural sphere—evaluation of evidence, loss of employment capacity, legal capacity, and protection against domestic violence—and in the healthcare system—right to health and obstetric violence. Our purpose is to make their experiences visible, quantify and qualify the barriers they face, and propose protocols and regulatory recommendations that guarantee their effective access to justice and dignified healthcare. At the regulatory level, Colombia has taken significant steps toward integrating a gender perspective.